EXPLORING THE RISE OF MENTAL HEALTH ISSUES AMONG YOUTH IN INDIA: POST-PANDEMIC EFFECTS - Margala Juang Bertorio; Theerka. N. (JTH: Journal of Technology and Health, 2025)
The COVID-19 pandemic has had a profound impact on the mental health of youth globally, and this study investigates its effects on youth in India, with a particular focus on rural versus urban disparities. The study employed a mixed-methods approach, combining quantitative surveys and qualitative interviews to assess the prevalence of anxiety, depression, and stress among youth. Results indicate that rural youth face significantly higher levels of mental health issues compared to urban counterparts, with anxiety and depression rates reaching 58% and 51%, respectively, compared to 45% and 43% in urban areas. The study also explored the role of digital health platforms in mental health care, finding that urban youth have better access to such resources. The qualitative data further revealed that rural youth rely heavily on informal support systems, such as family and religious leaders, as opposed to formal mental health services. This study highlights the urgent need for targeted mental health interventions, particularly in rural areas, and the integration of digital platforms into the mental health care system to bridge the gap between urban and rural regions. By addressing these disparities, India can move towards more equitable mental health care for its youth population.